Active sound and vibration control theory and applications - Tokhi, M. O.; Veres, Sándor M. 1956- (Institution of Engineering and Technology, 2002)
The book has 3 parts which are further divided into 15 chapters. The first part deals with the fundamental reviews of active sound control and vibration control . The second part covers algorithms for active noise control and vibration control and third part covers application of active noise control and vibration control.